From usage value to the symbolic value of objects: Masks in times of pandemic - Portilla Luja, María de las Mercedes; Morales González, Celia Guadalupe (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
Reconfiguring the dynamics of life became a necessary reality due to COVID-19; most of the population did not visualize what we face today. Breaking with existing paradigms around derived activities from forced confinement and the use of masks, has given relevance to the image as the basic language in the face of social distancing. The objective of this work is to interweave symbolic representations and the need for human beings to integrate themselves into a society, through the processes of meaning and symbolic elements, to weave cohesion or to unravel social relationships.